Early selexipag initiation and long-term outcomes: insights from randomised controlled trials in pulmonary arterial hypertension - Coghlan, J. Gerry; Gaine, Sean; Channick, Richard; Chin, Kelly M.; du Roure, Camille; Gibbs, J. Simon R.; Hoeper, Marius M.; Lang, Irene M.; Mathai, Stephen C.; McLaughlin, Vallerie V.; Mitchell, Lada; Simonneau, Gérald; et al. (ERJ open research, 2023)
Further understanding of when to initiate therapies in pulmonary arterial hypertension (PAH) is important to improve long-term outcomes. Post hoc analyses of GRIPHON ( NCT01106014 ) and exploratory analyses of TRITON ( NCT02558231 ) suggested benefit of early selexipag initiation on long-term outcomes, despite no additional benefit versus initial double combination on haemodynamic and functional parameters in TRITON. Post hoc analyses investigated the effect of early selexipag initiation on disease progression and survival in a large, pooled PAH cohort. Data from newly diagnosed (≤6 months) PAH patients from GRIPHON and TRITON were pooled. Patients on active therapy with selexipag (pooled selexipag group) were compared with those on control therapy with placebo (pooled control group). Disease progression end-points were defined as per the individual studies. Hazard ratios (HR) and 95% CI for time to first disease progression event up to end of double-blind treatment (selexipag/placebo) +7 days and time to all-cause death up to end of study were estimated using Cox regression models. The pooled dataset comprised 649 patients, with 44% on double background therapy. Selexipag reduced the risk of disease progression by 52% versus control (HR: 0.48; 95% CI: 0.35–0.66). HR for risk of all-cause death was 0.70 (95% CI: 0.46–1.10) for the pooled selexipag versus control group. Sensitivity analyses accounting for the impact of PAH background therapy showed consistent results, confirming the appropriateness of data pooling. These post hoc , pooled analyses build on previous insights, further supporting selexipag use within 6 months of diagnosis, including as part of triple therapy, to delay disease progression.